Imagem de produto : a configuração da imagem do vinho fino - Toigo, Taisson (My University, 2014)
International trading has become a common activity in global economics. According to information of Brazilian Wine Institute (IBRAVIN) 80% of the sold wine in Brazil are imported. Product image plays as important role on preferences and product choice (CHUANG; CHANG; HSU, 2001), as long as the choice hardly depends on product`s image perpeption. The purpose of this study was to identify the nacional and imported wine`s configuration of image an d the determinant factors on purchase intent over customers across Serra region of Rio Grande do Sul.Therefore, after the literature review on the subjects, an exploratory qualitative research was conducted, through semi-structured interviews aiming to identify the attributes that compose the wine`s image. Next, a quantitative research was handled through a survey, using statistical techniques like Analysis of Variance (ANOVA), factor analysis and multiple linear regression. Through the factor analysis it was possible to obtain 6 dimensios of wine image: (i) symbolic, (ii) social-simbolic, (iii) affective-sensory, (iv) value, (v) functional and (vi) historic. By the multiple linear regression it was not possible to obtain relevant results. It was also found two new factors by the factorial analisys: (ii)social-simbolic and (vi)historic. So, the understanding on the wine image becomes better. [resumo fornecido pelo autor]
Segundo dados do Intituto Brasileiro do Vinho (Ibravin), de cada cinco vinhos finos vendidos no Brasil, 80% é importado. A imagem de um produto tem um papel importante na preferência e na escolha do produto (CHUANG; CHANG; HSU, 2001), uma vez que a escolha depende largamente da percepção sob a imagem do produto. Assim sendo, o objetivo central deste estudo foi de identificar a configuração da imagem do vinho fino nacional e importado e os fatores determinantes nas intenções de compra dos consumidores da região serrana do Rio Grande do Sul. Para isso, realizou-se uma pesquisa qualitativa de caráter exploratório, através de entrevistas semi-estruturadas para identificar os atributos que compõem a imagem do vinho fino. Após, conduziu-se uma pesquisa quantitativa, através de uma survey, onde utilizou-se técnicas estatísticas como Análise de Variancia (ANOVA), analise fatorial e regressão linear múltipla. Através da analise fatorial foi possível a obtenção de 6 fatores que compõem a imagem do vinho fino: (i) simbólico, (ii) simbólico-social, (iii) afetivo-sensorial, (iv) valor, (v) funcional e (vi) histórico. A análise de regresso linear múltipla não mostrou resultados significantes. Os resultados da análise de regressão indicam os fatores (ii) simbólico-social e (vi) históricos como fatores novos na literatura. Assim, melhora-se o entendimento acerca da composição da imagem do vinho fino. [resumo fornecido pelo autor]
Keywords: Marketing; Comportamento do consumidor; Vinho; Wine; Product Image; Consumer behavior